Avoiding the Problem: A study on the generalisation of avoidance behaviour - Fisher, Courteney Tiegan Louise (2025)
Anxiety disorders are the most common mental health conditions worldwide, affecting over 61 million people in Europe alone. Since the COVID-19 pandemic, these numbers have risen, with a growing prevalence among younger individuals and children. Avoidance is a defining characteristic of all anxiety disorders, yet it has remained relatively understudied due to an overemphasis on fear mechanisms. However, recent years have seen a resurgence of research in this area. Studies suggest that avoidance is a strong predictor of treatment outcomes and may be the missing link in improving current therapeutic approaches. Understanding avoidance behaviour can provide valuable insights into the underlying mechanisms of anxiety. One prominent notion in the literature is that anxiety may stem from the overgeneralisation of fear, that is when fear extends beyond the original threat to similar stimuli. This is a well-documented phenomenon, with research consistently showing that individuals with high trait anxiety or anxiety disorders exhibit heightened fear generalisation. It has been proposed that avoidance behaviour may function similarly, leading individuals to avoid situations and stimuli resembling the original fear-inducing experience. While research indicates that fear and avoidance are distinct processes, studying generalisation in avoidance behaviour is essential for a more comprehensive understanding of anxiety and its treatment. The goal of this thesis was to understand different aspects of avoidance behaviour with a focus on generalisation. We developed tasks to study avoidance behaviour both online and within the laboratory, so that a range of experiments could be conducted with different populations. Strictly speaking, we assessed different sources of generalisation of avoidance behaviour, by manipulating warning signals, stress, safety signals, and the context. Chapter 1 gives an introduction and literature review of research within anxiety, avoidance and generalisation. This gives an overview of current research and highlights the gaps within the field. In addition, Chapter 5 presents a review on relief and the role that signals associated with it play in avoidance behaviour. This also links with the safety signals aspect of the thesis. Chapter 2 assessed whether the contiguity between the warning signals and an aversive outcome can influence the shape of the generalisation gradient. The hypothesis based on previous literature was that a trace procedure would result in a broader generalisation gradient relative to a delay procedure. Interestingly, for individual differences in trait anxiety, the immediate (delay) condition was more sensitive to detecting differences based on trait anxiety levels compared to the trace group. Chapter 3 assessed whether perceived or induced stress have an effect on the generalisation of avoidance behaviour. These experiments found that neither perceived nor induced stress influence the generalisation of avoidance. Chapter 4 revealed that age can influence the shape of a gradient using a Space Invaders avoidance task in children. This was one of the first experiments assessing avoidance generalisation in children aged 5-11 years old. Chapter 6 investigated safety signals and the concept of relief. These experiments showed first that safety signals reinforce avoidance behaviour. In addition, such reinforcement can generalise to similar safety signals, but not to dissimilar signals. This was the first study to investigate the reinforcing properties of safety signals within humans. Finally, Chapter 7 investigated the generalisation of avoidance behaviour to variations in contextual cues (background colour) and documented a systematic relationship between avoidance behaviour and the similarity of testing to training contexts. Across experiments, there were no meaningful relationships between the generalisation (in its different forms) of avoidance behaviour and participant’s trait anxiety levels. Overall, this thesis demonstrates that different factors can influence avoidance behaviour in terms of warning signals, safety signals and the context. Together, these results provide insights into the underlying mechanisms of avoidance behaviour and sheds light on the potential effects of individual differences such as stress and anxiety. The findings of this thesis provide a much need understanding on the factors that affect generalisation of avoidance behaviour in humans. This knowledge could potentially assist clinicians when developing treatments and interventions that include avoidance as well as fear.